Dataset of the assessment of on-farm sustainability of vegetable farms in Benin Republic using the IDEA framework - Odjo, Sylvanus; Fassinou Hotegni, Nicodeme V.; Guidimadjègbè, Alexandre Nouhougan; Ayenan, Mathieu Anatole Tele; Singh, Ravi Gopal (International Maize and Wheat Improvement Center, 2024)
The International Maize and Wheat Improvement Center (CIMMYT), the University of Abomey-Calavi, Benin and the World Vegetable Center conducted a survey in Benin in March 2023 to assess the on-farm sustainability of vegetable farms. A matrix of indicators was built around the three dimensions of sustainability (ecological, social and economic) using the “Indicateur de Durabilité des Exploitations Agricoles” (IDEA) framework. The dataset contains the following information: (1) general information on the farm owner; (2) presentation of the farm (production means, methods, and processes); (3) IDEA indicators scores in the three dimensions; ecological (components: ecological diversity, organization of spaces and agricultural practices), Social (components: production management, employment and local development, ethics and human development), and economic sustainability (components: viability, transmissibility, autonomy and efficiency). (2024-05-09)